Comparison Between Age-Related Macular Degeneration And Polypoidal Choroidal Vasculopathy Using Optical Coherence Tomography - Masood, Seemal; Qamar Rao, Muhammad Rashad; Tayab, Fatima; Ur Rehman, Rai Farooq (Biological and Clinical Sciences Research Journal, 2025)
Age-Related Macular Degeneration (ARMD) and Polypoidal Choroidal Vasculopathy (PCV) are retinal conditions leading to central vision loss, especially in older individuals. Differentiating between these two conditions is critical for proper management, and Optical Coherence Tomography (OCT), particularly with OCT Angiography (OCTA) and Enhanced Depth Imaging (EDI) OCT, plays a key role in their diagnosis. Despite the availability of these advanced imaging techniques, PCV often remains undiagnosed, especially in resource-limited regions. Objective: This study compared the qualitative and quantitative features of ARMD and PCV using OCT and OCTA to enhance our understanding of their differences and promote accurate diagnosis, especially in settings where OCTA is underutilized. Methods: A retrospective study was conducted at Lahore Eye Care Center and Nishtar Hospital, Multan, from February to August 2024. Forty-three patients diagnosed with ARMD and PCV were included. The inclusion criteria required the presence of characteristic OCT findings, while patients with conditions such as diabetic retinopathy or retinal detachment were excluded. OCT measurements of central subfoveal and parafoveal thickness were used to quantify macular changes. Qualitative analysis focused on drusen, retinal pigment epithelium (RPE) elevation, and choroidal neovascularization (CNV) for ARMD and macular thickening and RPE irregularities for PCV. Results: The study revealed that patients with PCV exhibited significantly higher central subfoveal and parafoveal thicknesses than those with ARMD. Central subfoveal thickness in PCV was greater than 290 microns, while in ARMD, it was less than 250 microns. Parafoveal thickness was also thicker in PCV, with values exceeding 290 microns, compared to ARMD, which was below 270 microns. Qualitative features, including irregular RPE and ring-like lesions, were more prominent in PCV. Conclusion: This study demonstrates that OCT and OCTA are invaluable tools in differentiating ARMD from PCV, with distinct differences in qualitative and quantitative features. The findings underscore the need for greater awareness and access to OCTA, particularly in developing countries where PCV remains underdiagnosed. Early and accurate diagnosis through OCT and OCTA can significantly improve management outcomes for patients with these conditions.